Perhitungan Umur Pakai Lapisan Teflon pada Permukaan Prototype Alat Masak dari Ketahanan Aus Terhadap Gesekan Sutil - Bayu Aji, Alam Prasetya; Suyitno, Suyitno; Hilm, Fuad y (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
Teflon-coated cookware is a disposable product because its use involves an inevitable physical destruction process. The wear and tear of the glaze during the cooking process is one of the physical destruction processes that cause damage to the teflon coating. The time until the occurrence of damage to the teflon coating due to wear from the friction of the utensil can be used to calculate the service life of the teflon coating. This study uses the Weibull distribution method to calculate the service life of the teflon coating on the cookware prototype, with the calculation results showing an expected lifespan of about 20,335.5 friction with a reliability level of 47%. The results of these calculations are a description of the specifications of the service life of the Teflon coating on the cookware prototype that will be used in household kitchens.